Development and collaborative validation of an event-specific quantitative real-time PCR method for detection of genetically modified CC-2 maize - Long, Likun; Zhao, Ning; Li, Congcong; He, Yuxuan; Dong, Liming; Yan, Wei; Xing, Zhenjuan; Xia, Wei; Ma, Yue; Xie, Yanbo; Liu, Na; Li, Feiwu (Frontiers in Plant Science, 2024)
As one of the developed genetically modified (GM) maize varieties in China, CC-2 has demonstrated promising commercial prospects during demonstration planting. The establishment of detection methods is a technical prerequisite for effective supervision and regulation of CC-2 maize. In this study, we have developed an event-specific quantification method that targets the junction region between the exogenous gene and the 5' flanking genomic DNA (gDNA) of CC-2. The accuracy and precision of this method were evaluated across high, medium, and low levels of CC-2 maize content, revealing biases within ±25% and satisfactory precision data. Additionally, we determined the limits of quantification of the method to be 0.05% (equivalent to 20 copies) of the CC-2 maize. A collaborative trial further confirmed that our event-specific method for detecting CC-2 produces reliable, comparable, and reproducible results when applied to five different samples provided by various sources. Furthermore, we calculated the expanded uncertainty associated with determining the content level of CC-2 in these samples.